Study on Interstage Pressure Equalization of Differential Multi-Stage Finger Seal with Structural Design, Flow and Heat Transfer Characteristics - Juan Wang; Wei Xu; Meihong Liu; Shixing Zhu; Yuchi Kang; Xiaolei Song; Dianhai Gu; Xuefeng Hu (Aerospace)
To effectively address the issue of premature failure caused by the unbalanced distribution of pressure drops between the stages of a traditional two-stage finger seal, this study proposes a method to improve the pressure drop balance by increasing the protection height of the second stage back plate. We established a new numerical calculation model for a two-stage finger seal, based on the porous media model. After verifying the precision of the model, we conducted a numerical analysis to examine the impact of the protection height of the second stage back plate on the flow and heat transfer characteristics of the two-stage finger seal. We then conducted a differentiated structural design for each stage of the two-stage finger seal. The research results are as follows: the pressure drop at the second stage of the traditional two-stage finger seal exceeds that of the first stage; when the protection height of the second stage back plate of the traditional two-stage finger seal is increased from 1.5 mm to 1.57 mm, forming a two-stage pressure equalizing finger seal structure, the pressure drop between the two stages is balanced, but the leakage is greater than that of the traditional two-stage finger seal; a grate seal structure was arranged between the first and second stages of the two-stage pressure equalizing finger seal to form a two-stage pressure equalizing finger seal with grate teeth, which exhibits significantly lower leakage compared to the two-stage pressure equalizing finger seal. However, the proportion of pressure drop at the first and second stages of the two-stage pressure equalizing finger seal is 36.8% and 42.1%, respectively, while the grate tooth stage accounts for 21.1%, resulting in an imbalanced pressure drop once again. Increasing the protection height of the second stage back plate in the two-stage pressure equalizing finger seal with grate teeth to 1.6 mm results in a 37.5% pressure drop at the first and second stages, and a 25% pressure drop at the grate tooth stage. The two-stage finger seal balances the pressure drop and matches the leakage of the traditional two-stage finger seal. The maximum temperatures of the first and second stages of the finger seal are 0.7% lower and 2.6% higher compared to the traditional two-stage finger seal. This suggests that a differential multi-stage finger seal is the optimal structure.